38 views
Let A= (a + b)* ab (a + b)*, B= a*b* and C= (a + b)*. Then the relation between A, B and C:

A. A+B= C
B. $A^{R}+B^{R}=C$
C. $A^{R}$+B= C
D. None of these
| 38 views
0
0
@hirak does not care abt ashok dinda type questions. He always waits for the Dale Steyn type questions........ hirak will set things on fire during exm.
0
@user2525

ato chatle eibar forsa hoe jabo.. XD
0
Accha ........ forsa de villiers er moto batting korbi r ki ..... :P
+1
sei sei… ( IITD laughs in background)
+1
Prohibited flag incoming….XD

by (1.2k points)

A generates strings with ab as substring and B generates strings of form a*b*.

Reversal of A be AR:

Let A = X(YX) where X = ( a + b )* and Y = ab

AR = ( X(YX))R = (YX)R XR = XR YR XR = (a+b)*R (ab)R ( a+b)*R = (a+b)*ba (a+b)*

AR = ( a+ b)*ba( a+b)*

Now do the union of AR and B u will get all the strings in ( a+b)* i.e. in C.
Because in A + B u will never get ba which is in C. So, just reverse A and u will get strings containing ba.
by (1.6k points)
0
All previous years questions are already available on gateoverflow.in so before posting any question search for the availability of the same. If you are unable to find please mention the source while posting.